Processos educativos para a emancipação e a cidadania de pessoas idosas: olhares sobre políticas públicas no município de Vacaria, Rio Grande do Sul - Scopel, Eliete Maria (Universidade do Vale do Rio dos Sinos, 2021)
This thesis is the result of the development of my doctoral research associated with the area of study called Education, History, and Policies, part of the Graduate Program in Education at Unisinos University. This research articulates the following themes: aging, education and public policies for the elderly, and the object of study is composed by the educational processes, the citizenship and the emancipation of the elderly. Also, the general objective is the analysis of the actions and programs directed to these people, developed by the Service of Coexistence and Strengthening of Bonds (SCFV), in the city of Vacaria, while strategies for the citizenship development and the political emancipation of the elderly. In addition, the specific objectives are: 1) characterize regulations for aging in international and national scope, in the perspective of social rights and their influence in the public policy intended to the elderly population in Vacaria; 2) contextualize the city of Vacaria and outline the demographic profile of the longlived who attend the actions and programs developed by the SCFV; and 3) analyze the education processes in programs and actions by the SCFV of Vacaria, regarding the difficulties and the potentialities for the citizenship development and the emancipation of elderly people. Therefore, we adopted the qualitative methodological perspective, using the historicaldialectical method, in which 13 participants were selected as research subjects: five professionals who act directly or indirectly with the elderly population in the SCFV of Vacaria’s Social Development Office and eight long-lived coordinators of the coexistence groups registered in the SCVF of Vacaria. As the data collection instrument, we use legislations of international, national and local nature, related to the public policy directed to the elderly population, and also a semi-structured interview. In order to interpret the data obtained, I resorted to the technique of document and content analysis. Our results show that, although the public policies for the elderly in Vacaria were implemented aiming at a welfare objective, as the time went by, they have evolved, so that the elderly population has been conquering fundamental and social rights – these, however, still do not correspond to the totality of rights prescribed by the Brazilian National Policy for the Elderly and the Elderly Statute. Besides that, it was possible to identify which actions and/or activities carried out in the coexistence groups contribute to the biopsychosocial development of participants, such as the fact that the coexistence groups can be considered social spaces that trigger education processes to human formation, through the exchange of experiences, sociability and listening, favoring citizenship development and emancipation of the elderly.
Keywords: Política pública para idoso; Cidadania; Emancipação; Pedagogia social; Processos educativos; Public policy for the elderly; Citizenship; Emancipation; Social pedagogy; Educational processes; ACCNPQ::Ciências Humanas::Educação